'Chinese' hegemony from a Korean shi perspective: aretocracy in the early modern East Asia. (14th December 2020) - Choi, Inho
Abstract: The study of pre-modern Chinese hegemony is crucial for both theorizing hegemony and envisioning a new global order. I argue the pre-modern Chinese hegemony was a reciprocal rule of virtue, or aretocracy, driven by the transnational sociocultural elites shi . In contrast to the prevailing models of Chinese hegemony, the Early Modern East Asia was not dominated by the unilateral normative influence of the Chinese state. The Chinese and non-Chinese shi as non-statist sociocultural elites co-produced, through their shared civilizational heritage, a hegemonic order in which they had to show excellence in civil virtues to wield legitimate authority. In particular, the Ming and Chosŏn shi developed a tradition of envoy poetry exchanges as a medium for co-constructing Chinese hegemony as aretocracy. The remarkable role of excellent ethos for world order making in Early Modern East Asia compels us to re-imagine how we conduct our global governance.